What is the most appropriate knowledge synthesis method to conduct a review? Protocol for a scoping review - Kastner, Monika (BioMed Central, 2012)
BACKGROUND: A knowledge synthesis attempts to summarize all pertinent studies on a specific question, can improve the understanding of inconsistencies in diverse evidence, and can identify gaps in research evidence to define future research agendas. Knowledge synthesis activities in healthcare have largely focused on systematic reviews of interventions. However, a wider range of synthesis methods has emerged in the last decade addressing different types of questions (e.g., realist synthesis to explore mediating mechanisms and moderators of interventions). Many different knowledge synthesis methods exist in the literature across multiple disciplines, but locating these, particularly for qualitative research, present challenges. There is a need for a comprehensive manual for synthesis methods (quantitative/qualitative or mixed), outlining how these methods are related, and how to match the most appropriate knowledge synthesis method to answer a research question. The objectives of this scoping review are to: 1) conduct a systematic search of the literature for knowledge synthesis methods across multi-disciplinary fields; 2) compare and contrast the different knowledge synthesis methods; and, 3) map out the specific steps to conducting the knowledge syntheses to inform the development of a knowledge synthesis methods manual/tool. METHODS: We will search relevant electronic databases (e.g., MEDLINE, CINAHL), grey literature, and discipline-based listservs. The scoping review will consider all study designs including qualitative and quantitative methodologies (excluding economic analysis or clinical practice guideline development), and identify knowledge synthesis methods across the disciplines of health, education, sociology, and philosophy. Two reviewers will pilot-test the screening criteria and data abstraction forms, and will independently screen the literature and abstract the data. A three-step synthesis process will be used to map the literature to our objectives. DISCUSSION: This project represents the first attempt to broadly and systematically identify, define and classify knowledge synthesis methods (i.e., less traditional knowledge synthesis methods). We anticipate that our results will lead to an accepted taxonomy for less traditional knowledge synthesis methods, and to the development and implementation of a methods manual for these reviews which will be relevant to a wide range of knowledge users, including researchers, funders, and journal editors.